Neurobrucellosis with negative serological examination: a case report and literature review - Yuan, Boyao; Jiang, Taotao; Han, Jingjing; Wang, Manxia (Frontiers in Medicine, 2025)
Neurobrucellosis is an uncommon occurrence that can arise as a consequence of brucellosis. However, its clinical symptoms are severe and have the potential to be life-threatening. Timely detection, prompt diagnosis, and early treatment are crucial factors. Clinically, the gold standard for diagnosing pathogenic microorganisms is through culture. However, this method is hindered by its lengthy culture duration, low rate of positive results, and the absence of typical clinical signs of neurobrucellosis. Consequently, misdiagnosis and delayed treatment are common. Metagenomics next-generation sequencing (mNGS) technology is a novel approach in microbiological diagnosis that enables the simultaneous detection of all microorganisms present in a sample, including viruses, bacteria, fungus, and parasites. This method holds significant diagnostic significance for viral disorders affecting the central nervous system. This paper reports a case of neurobrucellosis detected by mNGS after a negative serological test, as well as a review of the relevant literature.